2017
DOI: 10.13060/00380288.2017.53.6.377
|View full text |Cite
|
Sign up to set email alerts
|

Narratives and Practices of Voluntary Simplicity in the Czech Post-Socialist Context

Abstract: Voluntary simplicity is usually seen as an alternative social movement that is responding to the current social and environmental crisis within affluent societies. Many scholars draw on Inglehart's concept of post-materialism and consider voluntary simplicity to be a way of limiting one's consumption in order to free oneself and seek satisfaction in the non-material aspects of life. These scholars assume that the values associated with simplicity emerge out of over-saturation with consumption. This article dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
1
13
0
2
Order By: Relevance
“…This analysis shows that the majority of VS studies have been conducted in developed countries and especially in Anglo-Saxon countries (Figure 5). Although this finding may partially be due to the fact that our search was conducted in English, this result suggests that there is a need to study this lifestyle in diverse geographical locations, including developing and emerging countries (Kraisornsuthasinee & Swierczek, 2018), as VS is not exclusive of affluent people and developed countries (Huneke, 2005;Kala et al, 2017).…”
Section: Study Locationmentioning
confidence: 94%
See 1 more Smart Citation
“…This analysis shows that the majority of VS studies have been conducted in developed countries and especially in Anglo-Saxon countries (Figure 5). Although this finding may partially be due to the fact that our search was conducted in English, this result suggests that there is a need to study this lifestyle in diverse geographical locations, including developing and emerging countries (Kraisornsuthasinee & Swierczek, 2018), as VS is not exclusive of affluent people and developed countries (Huneke, 2005;Kala et al, 2017).…”
Section: Study Locationmentioning
confidence: 94%
“…The 'voluntary' nature of the adoption of a simple lifestyle excludes the practices from those who have no freedom of choice, who live in forced poverty or are coerced by any institution or government to adopt such behaviours (Boujbel & d'Astous, 2012;Elgin & Mitchell, 1977;Etzioni, 2004;Gambrel & Cafaro, 2010;Leonard Barton, 1981;McDonald et al, 2006;Shama & Wisenblit, 1984). Some studies hold that VS is not exclusive of affluent people, this lifestyle can also be chosen by those whose basic needs are less well satisfied (Huneke, 2005;Kala et al, 2017).…”
Section: Voluntary S Impli Cit Ymentioning
confidence: 99%
“…These people have been studied by Hana Librová [1994Librová [ , 2003Librová et al 2016], who frames their activities through the concepts of voluntary simplicity, ecological luxury, and the generational transmission of simplicity. Librová et al [2016: 264] and her students Kala, Galčanová, and Pelikán [2017] argue that Czechs who practise the environmentally-friendly lifestyle of voluntary simplicity do so intuitively, and they found that the participants in their research ('the colourful') could not be identified with any movement. The argument that these people do not identify with any movement is based on a research sample from 1992, before transnational movements had spread to Czechoslovakia.…”
Section: Eastern Europe and The Transition Movementmentioning
confidence: 99%
“…Binka 2010; Fagan 2004; Novák 2017). Stejně tak se environmentálně příznivý životní styl stal předmětem řady studií, zejména ve spojitosti s dobrovolnou skromností, ekologickým luxusem a generačním přenosem skromného života (Librová 1994;2003;Librová et al 2016;Kala -Galčanová -Pelikán 2017). Hana Librová (2016: 264) poukazuje na to, že environmentálně příznivý životní způsob zkoumaných Čechů byl intuitivní a účastníci výzkumu ("pestří") nemohou být spojováni s žádným hnutím.…”
Section: Kulturní Kreativci V čEsku: Stav Zkoumáníunclassified